2022
DOI: 10.3389/fncel.2022.1005399
|View full text |Cite
|
Sign up to set email alerts
|

Application and prospects of somatic cell reprogramming technology for spinal cord injury treatment

Abstract: Spinal cord injury (SCI) is a serious neurological trauma that is challenging to treat. After SCI, many neurons in the injured area die due to necrosis or apoptosis, and astrocytes, oligodendrocytes, microglia and other non-neuronal cells become dysfunctional, hindering the repair of the injured spinal cord. Corrective surgery and biological, physical and pharmacological therapies are commonly used treatment modalities for SCI; however, no current therapeutic strategies can achieve complete recovery. Somatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 158 publications
0
6
0
Order By: Relevance
“…Proinflammatory cells are then activated, releasing abundant inflammatory cytokines, which induce a cascade of secondary injury[ 82 ]. Many neurons, astrocytes, and other neural cells die in the injured area due to necrosis or apoptosis during the secondary injury[ 83 ]. Until now, current clinical strategies have not achieved satisfactory outcomes due to irreversible damage to neural cells.…”
Section: Therapeutic Potentials Of Dental Follicle Stem Cells In Neur...mentioning
confidence: 99%
“…Proinflammatory cells are then activated, releasing abundant inflammatory cytokines, which induce a cascade of secondary injury[ 82 ]. Many neurons, astrocytes, and other neural cells die in the injured area due to necrosis or apoptosis during the secondary injury[ 83 ]. Until now, current clinical strategies have not achieved satisfactory outcomes due to irreversible damage to neural cells.…”
Section: Therapeutic Potentials Of Dental Follicle Stem Cells In Neur...mentioning
confidence: 99%
“…The use of stem cells isolated from different body tissues such as bone marrow, placenta, olfactory tissues, and the CNS itself has seen extensive application for spinal cord repair strategies. [191,192] With the advent of somatic cell reprograming for example, using retroviral transduction of Oct4, Sox2, Klf4, and c-Myc to generate induced pluripotent stem cells (iPSCs) has provided an expandable source of patient-specific progenitor cells for autologous transplantation to the injured cord [193] without the need for immunosuppression. [194] While the interactions of transplanted stem cells with host injured cord are generally beneficial, [195] the results from several clinical trials have reported mixed results.…”
Section: Therapeutic Gene Delivery To Stem Cellsmentioning
confidence: 99%
“…Zarei-Kheirabadi et al. demonstrated more efficient reprogramming with zinc finger protein 521 (Zfp521) in comparison to Sox2, with motor neuron-evoked potentials observed and improvements in motor function [120 , 121] . Neurogenin2 (Ngn2) converted astrocytes specifically into glutamatergic and GABAergic neurons with induced neurons able to respond to inputs from the dorsal root ganglion [122] .…”
Section: Promoting Regeneration After Scimentioning
confidence: 99%
“…used CRISPRa to activate expression of Ngn2 and Islet-1 (Isl1) in vitro and in vivo. ROCK inhibitor Y-27632 administration allowed for improved motor neuronal maturation and branching to the sciatic nerves [120 , 125] . dCas9 is a mutant nuclease deactivated form of Cas9 that can be used to either augment or decrease gene expression without disruption of the DNA strands [113] .…”
Section: Promoting Regeneration After Scimentioning
confidence: 99%